2010
DOI: 10.2320/matertrans.maw201026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extrusion Parameters on Mechanical Properties of Mg<SUB>97</SUB>Zn<SUB>1</SUB>Y<SUB>2</SUB> Alloys at Room and Elevated Temperatures

Abstract: The effects of alloy extrusion parameters, such as extrusion ratio, temperature, and speed on the mechanical properties at room and elevated temperatures and the microstructure evolution were investigated in the production of high strength Mg-Zn-Y alloys. The alloy used is a Mg 97 Zn 1 Y 2 (at%) which is engineered to acquire a long-period stacking ordered (LPSO) structure phase to increase alloy-strength. The microstructure of the extruded Mg 97 Zn 1 Y 2 alloy consists of hot-worked and dynamically recrystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 26 publications
5
28
0
Order By: Relevance
“…This suggests that the initial grain size of the billet has a negligible effect on the DRXed grain size of an extruded alloy, even though this is known to be strongly affected by extrusion parameters such as temperature and speed. [1,2] This insensitivity of the DRXed grain size to initial grain size is consistent with previous results obtained with Mg-3Al-1Zn alloy. [16] It can also be seen that there are a number of fine Mg 17 Al 12 precipitates (100 to 500 nm) distributed along the grain boundaries and within the grains of both samples (Figures 4(a) and (b)).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that the initial grain size of the billet has a negligible effect on the DRXed grain size of an extruded alloy, even though this is known to be strongly affected by extrusion parameters such as temperature and speed. [1,2] This insensitivity of the DRXed grain size to initial grain size is consistent with previous results obtained with Mg-3Al-1Zn alloy. [16] It can also be seen that there are a number of fine Mg 17 Al 12 precipitates (100 to 500 nm) distributed along the grain boundaries and within the grains of both samples (Figures 4(a) and (b)).…”
supporting
confidence: 93%
“…The microstructure and mechanical properties of extruded Mg alloys are known to be strongly dependent on extrusion variables; i.e., a decrease in deformation temperature, ram speed, and/or extrusion ratio generally results in a reduction in the size of dynamically recrystallized (DRXed) grains and a subsequent increase in strength. [1][2][3] In addition to these extrusion parameters, the microstructure of a billet prior to extrusion can also play an important role in determining the microstructure and mechanical properties of the final product. For example, twins initially present in a homogenized billet can increase the fraction of DRXed regions by acting as nucleation sites during extrusion, thereby improving the tensile properties of an extruded Mg alloy.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] The strengthening mechanisms of Mg/LPSO two-phase alloys were recently discussed in detail, and it was reported that controlling the morphology and texture of the LPSO-phases is important 9,12) because the LPSO-phase exhibits strong plastic anisotropy. [13][14][15] Previously, we have examined the plastic deformation behavior of an LPSO-phase with a 18R-typed crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The average equivalent strain was calculated using the equation ε = lnR, 11) neglecting the shear deformation, where R is the extrusion ratio. From this equation, the average equivalent strain (ε ) was 1.1 for an extrusion ratio of 3 and 1.9 for an extrusion ratio of 7.…”
Section: Effect Of Extrusion Ratiomentioning
confidence: 99%